Sams teach yourself Android application development in 24 hours - Delessio, Carmen; Darcey, Lauren, 1977-; Conder, Shane, 1975- (Indianapolis, Indiana : Sams, 2013)
With the arrival of next-generation phones like Droid, Android has established itself as a world-leading mobile development platform. This is a friendly, accessible guide to Android development for every programmer with a working knowledge of Java.
Includes index.
Formerly CIP.
Keywords: Android (Electronic resource); Application software -- Development